1979
DOI: 10.1080/00288233.1979.10420841
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin inhibitor contents of lupin seeds and other grain legumes

Abstract: Analyses for trypsin inhibitor were carried out on a group of legume seed samples previously evaluated nutritionally in rat growth studies. Sweet lupin seeds tLupinus albus and L. angustifolius) had no detectable amount of inhibitor (less than 0.1 mg/g) . Glycine max (soya beans) had 26.2 mg/g. Phaseolus lunatus (lima beans) and three varieties of P. vulgaris had 10-20 mg/g; the variety called "pinto beans" had an inhibitor level within the range 2.0-3.5 mg/g shown by field peas (Pisum sativumi and broad beans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…Soybean has been extensively studied and used as reference, showing a 16.5-29 unit range (Collins and Sanders, 1976). TIA values for raw faba bean seeds found here agree with those reported in the literature by Soni et al (1978) and Hove and King (1979), who indicated TIA values of raw faba bean Values are means ( standard error of 10 Wistar rats. The same superscript in the same column indicates no significant differences (p e 0.05).…”
Section: Chemical Analysissupporting
confidence: 92%
“…Soybean has been extensively studied and used as reference, showing a 16.5-29 unit range (Collins and Sanders, 1976). TIA values for raw faba bean seeds found here agree with those reported in the literature by Soni et al (1978) and Hove and King (1979), who indicated TIA values of raw faba bean Values are means ( standard error of 10 Wistar rats. The same superscript in the same column indicates no significant differences (p e 0.05).…”
Section: Chemical Analysissupporting
confidence: 92%
“…The reduction of protein digestibility in soya and lupin seeds has been associated with the presence of protease inhibitors, as well as antinutritionals such as fibre and oligosaccharides . Sweet lupin seeds ( Lupinus albus and L. angustifolius ) have a much lower amount of inhibitor (<0.1 mg g −1 ) than soya beans (26.2 mg g −1 ) …”
Section: Introductionmentioning
confidence: 99%
“…Howard et al (1996) found a range of 0.32-2.57 mg g" 1 over 13 cultivars, andincludedvalues for 'Rex' and 'Bohatyr' of 0.55 and 2.57 mg g" 1 , respectively. Hove & King (1979) found a range of 1.9 to 3.5 mgg" 1 over three cultivars, but none of these was used in the present study. However, as these values from the literature were expressed as mg g" 1 , and the values in this study are reported as units mg" 1 these data are not directly comparable.…”
Section: Discussionmentioning
confidence: 98%
“…Trypsin inhibitor levels in other New Zealand cultivars of field peas have been determined (Hove & King 1979;Howard et al 1996). Howard et al (1996) found a range of 0.32-2.57 mg g" 1 over 13 cultivars, andincludedvalues for 'Rex' and 'Bohatyr' of 0.55 and 2.57 mg g" 1 , respectively.…”
Section: Discussionmentioning
confidence: 99%